Efeito do pré-resfriamento da água em placas porosas de sistemas de resfriamento evaporativo - Fernandes, João Levi Bastos (2020)
Thermal control inside several agricultural facilities is an issue that has required several researches. Thus, the aim of this study was to evaluate the pre-chilled water effect applied on porous plate of evaporative cooling systems. The experiment was carried out on two physical models built on a small and distorted scale with evaporative cooling through cellulose panels with wetting by chilled water (CWCS) and an identical system to the previous one, however with panel wetting by natural water (NWCS). Air dry-bulb temperature (tdb), black-globe temperature (tbg) and air relative humidity (RH) were measured inside of the physical models and the external environment at 10 seconds interval. Physical models represent agricultural facilities equipped with ventilation as negative pressure wind tunnel. From the measured data, the temperature-humidity index (THI), the black globe-humidity index (BGTH), the enthalpy (h) and the cooling effectiveness () were calculated in both physical models built in reduced scale. The pre-chilled water used in porous plates wetting of evaporative cooling systems provided a greater reduction in thermal variables and comfort indexes compared to wetting with water at room temperature.